Robotic Systems 2020
DOI: 10.4018/978-1-7998-1754-3.ch041
|View full text |Cite
|
Sign up to set email alerts
|

Single SNN Architecture for Classical and Operant Conditioning Using Reinforcement Learning

Abstract: A bio-inspired robotic brain is presented where the same spiking neural network (SNN) can implement five variations of learning by conditioning (LC): classical conditioning (CC), and operant conditioning (OC) with positive/negative reinforcement/punishment. In all cases, the links between input stimuli, output actions, reinforcements and punishments are strengthened depending on the stability of the delays between them. To account for the parallel processing nature of neural networks, the SNN is implemented on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…• HoLLiE arm [31] • FPGA ZEM4310, Emotive Epoc headset [23] • DVS, NAS [102] • UR3 with elbow and wrist [105] • Prosthetic hand [86] • Tobii Eye Tracker, YDLIDAR G4, Raspberry Pi 3 [100] Cognition and Learning [117] • Robotic hand, Myo armband, Epoc headset [25] [118] • Loihi, Neural Computer Stick2 [112] • Spartan-6, RGB sensor [113] • Raspberry Pi3, PiCamera, PiStrom [117] • Loihi, LIDAR [114] TABLE 6: Software/ simulators and neuron models for all the applications.…”
Section: Soundmanmentioning
confidence: 99%
See 3 more Smart Citations
“…• HoLLiE arm [31] • FPGA ZEM4310, Emotive Epoc headset [23] • DVS, NAS [102] • UR3 with elbow and wrist [105] • Prosthetic hand [86] • Tobii Eye Tracker, YDLIDAR G4, Raspberry Pi 3 [100] Cognition and Learning [117] • Robotic hand, Myo armband, Epoc headset [25] [118] • Loihi, Neural Computer Stick2 [112] • Spartan-6, RGB sensor [113] • Raspberry Pi3, PiCamera, PiStrom [117] • Loihi, LIDAR [114] TABLE 6: Software/ simulators and neuron models for all the applications.…”
Section: Soundmanmentioning
confidence: 99%
“…• SKAN [113] • SRM [111] VOLUME Furthermore Rast et al [28] made several enhancements to the basic networks and showed how they can be used to direct performance towards behaviourally relevant goals. They observed the behaviourally relevant STDP appears to contribute strongly to positive learning as compared to negative learning.…”
Section: Major Applicationsmentioning
confidence: 99%
See 2 more Smart Citations